Almost everywhere convergence of the spherical partial Fourier integrals for radial functions - Carro, Maria J. (Banach journal of mathematical analysis, 2010)
We study new conditions on a radial function f in order to have the almost everywhere convergence of the spherical partial Fourier integrals. 2000 Mathematics Subject Classification. Primary 26D10; Secondary 44B20, 42EB10. Key words and phrases. Fourier integrals, extrapolation theory, almost everywhere convergence, radial functions, Muckenhoupt weights.